Surface plasmon resonance as a tool for ligand-binding assay reagent characterization in bioanalysis of biotherapeutics. (5th April 2018) - Duo, Jia; Bruno, JoAnne; Kozhich, Alexander; David-brown, Donata; Luo, Linlin; Kwok, Suk; Santockyte, Rasa; Haulenbeek, Jonathan; Liu, Rong; Hamuro, Lora; Peterson, Jon E; Piccoli, Steven; et al.
Ligand-binding assay (LBA) performance depends on quality reagents. Strategic reagent screening and characterization is critical to LBA development, optimization and validation. Application of advanced technologies expedites the reagent screening and assay development process. By evaluating surface plasmon resonance technology that offers high-throughput kinetic information, this article aims to provide perspectives on applying the surface plasmon resonance technology to strategic LBA critical reagent screening and characterization supported by a number of case studies from multiple biotherapeutic programs.